Multi-mode tunable absorber based on graphene metamaterial. (November 2018) - Hu, Ning; Liu, Peiguo; Bian, Li-an; Zhou, Qihui; Liu, Chenxi; Zhang, Jihong; Liu, Hanqing
Abstract: In this paper, a novel design of metamaterial absorber (MA) with multi modes and tunability characteristics in terahertz (THz) range is presented. The MA consists of patterned gold-graphene on the top layer, graphene sheet and gold ground separated by SiO2 . The chemical potential of patterned graphene and graphene sheet can be tuned independently. Thus, the regulation flexibility of MA is greatly enhanced. For demonstration, the proposed MA is investigated using circuit analogy method and the distributions of the electric field are also discussed in detail to explore underlying mechanism. Numerical calculations are stimulated in a commercial full-wave solver and indicate that the proposed MA possesses excellent absorption properties. There are three perfect absorption ( ≥ 99.2 % ) modes at 2.4 THz, 4.2 THz and 7.2 THz respectively. Under the regulation of chemical potential, the proposed MA could serve as single-frequency or dual-frequency absorber without change of physical structure. When working as single-frequency absorber, the MA could be regulated between different modes during a large frequency range and the absorption peaks could also be regulated within the same mode during a relative smaller frequency range. Furthermore, the MA has two absorption peaks at 2.4 THz and 7.2 THz ( ≥ 95 % ) simultaneously as dual-frequency absorber. The proposed MA shows promising application potentials due to the flexible modulation and functions and this work provides a new perspective for the design of tunable THz absorbers based on graphene. Highlights: Multi perfect absorption modes. Could be regulated from single-frequency absorber to dual-frequency absorber though chemical potential. Absorption modes can be regulated. The absorption frequency could be modulated within the same mode.